The effect of indoor plants on students' effective learning levels - Karaelmas, Deniz (Journal of Asian Scientific Research, 2025)
The purpose of this study is to examine the role of indoor plants on students' learning levels. The study group consists of students studying in the Department of Interior Design at Zonguldak Bülent Ecevit University Çaycuma Vocational School. It was determined by the course instructor (researcher) that there were 40 interior design students in the 2024-2025 Spring semester when the study was conducted. A survey was administered to determine the effective learning levels of students in environments with and without plants. The survey was conducted in two stages. In the first stage, 30 students who participated in the study were given a lesson in an empty classroom and were asked to evaluate their learning in this classroom. In the second stage, indoor plants were placed in a classroom for the students. The placed plants remained in the classroom where these students were taking lessons until the end of the semester. The survey mentioned above was applied again at the end of the semester. The analyses revealed a significant difference between students' pre- and post-test scores regarding effective learning. Based on this result, it can be concluded that the use of indoor plants in classrooms significantly impacts students' learning levels.